Employee Performance: Worklife Balance to Maintain Organizational Commitment and Work Motivation - Putri Bayina Rahma Nurdin; Muzran Munizu; Sumardi Sumardi (Pascasarjana STIE Amkop Makassar, 2021)
Employee performance is very important to note so that the company's goals can be achieved according to quality and quantity. This study aims to analyze the extent of the effect of worklife balance on PT. Infomedia Nusantara Call Center Division 188 when it comes to the commitment of the organization and the extent of the work motivation of employees if it is associated with work motivation that boils down to efforts to improve employee performance. This type of research is quantitative research that looks for causal relationships between variables studied using 77 respondents whose questionnaire dissemination data is processed using SPSS and SmartPLS software. The results showed that employees who maintained worklife balance condition will be able to maintain their organizational commitment and still have a good organizational commitment so as to improve performance both directly as an influence of worklife balance and when organizational commitment and motivation are used as mediation variables. Keywords: Worklife balance, Organizational Commitment, Work Motivation, Employee